Creative problem solving for managers - Proctor, Tony. (London ; New York : Routledge, 1999)
Using case studies and case histories, together with extensive diagrams, examples and thought-provoking questions, this textbook provides the most up-to-date and extensive approach to creative problem solving.
Chapter 1 chapter one -- CREATIVITY AND ITS IMPORTANCE IN BUSINESS -- chapter 2 chapter two -- BLOCKS TO CREATIVITY -- chapter 3 chapter three -- THEORIES OF CREATIVITY AND THE CREATIVE PROBLEM SOLVING PROCESS -- chapter 4 Objective finding, fact finding and problem finding/definition -- OBJECTIVE FINDING, FACT FINDING AND PROBLEM FINDING/ DEFINITION -- chapter 5 Morphological analysis and related techniques -- MORPHOLOGICAL ANALYSIS AND RELATED -- chapter 6 chapter six -- BRAINSTORMING AND ITS VARIANTS -- chapter 7 chapter seven -- LATERAL THINKING AND ASSOCIATED METHODS -- chapter 8 chapter eight -- SYNECTICS -- chapter 9 chapter nine -- MISCELLANEOUS IDEATION -- chapter 10 chapter ten -- EVALUATION -- chapter 11 chapter eleven -- IMPLEMENTING IDEAS -- chapter 12 Computer assisted creative problem solving -- COMPUTER ASSISTED CREATIVE PROBLEM -- chapter 1 Case example of the creative problem solving process -- CASE EXAMPLE OF THE CREATIVE PROBLEM SOLVING -- chapter 2 appendix two / ADDITIONAL CASES -- chapter 3 appendix three / NOTES ON CASES AND PROBLEMS -- chapter 4 appendix four -- PUBLICATIONS.
Includes bibliographical references (pages 298-303)-and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Problem solving; Management; Problem Solving; Résolution de problème.; Gestion; management; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; Management; Problem solving